Oxidative Stress in Dairy Cattle: An Overview (Indian Journal of Animal Production and Management, 2024)
Throughout their productive lives, dairy cows experience numerous transitional phases that are  associated with increased metabolic and infectious disease susceptibility. Redox equilibrium is  crucial for guaranteeing a smooth transition. Nonetheless, oxidative stress (OS), a consequence of  redox imbalance, has been linked to a higher disease risk in these animals. The periparturient and  neonatal phases of the productive cycle of dairy cows are times of increased OS and disease  susceptibility. This article reviews the relationship of redox status and OS with diseases of cows and  calves, and how supplementation with various antioxidants can be used to prevent OS in these  animals.
Keywords: Oxidative stress; dairy cattle; antioxidant supplements